The Impact of Monetary Policy Instruments on Financial Stability: A Case Study of Iraqi Commercial Banks - Hasan, Barham Bakr; Vladimirovich, Girinsky Andrey; Mahmud, Mahmud Hedi Khalid (Unisia, 2025)
Since Iraqi commercial banks are so imperative to the country's economy, this consider looks at how money related approach instruments influence their capacity to preserve money related soundness. We utilize mixed-methods examination, combining subjective points of view from bank directors and policymakers with quantitative information from imperative money related measurements like resource quality, capital ampleness, and liquidity proportions. Based on their loaning capabilities and chance administration approaches, the comes about appear that save necessities and intrigued rate changes have a major effect on bank solidness. It too draws consideration to the specific troubles Iraqi banks have, like expansion and political unusualness that disturb the effect of financial arrangement. This investigates endeavors to move forward the proficiency of financial approach in advancing monetary steadiness in Iraq's keeping money industry by giving suggestions for policymakers.